Application of biochar from coconut and wood waste to reduce shrinkage and improve physical properties of silica fume-cement mortar. (30th November 2020) - Gupta, Souradeep; Krishnan, Padmaja; Kashani, Alireza; Kua, Harn Wei
Highlights: Biochar from uncontrolled combustion was thermally treated to improve its properties. Plastic and dynamic viscosity of cement composite increase with biochar porosity. 33% silica fume can be replaced by biochar without affecting permeability and strength. Addition of biochar reduces autogenous and drying shrinkage of silica fume-mortar. Biochar added at 5% cement replacement improve water tightness and strength. Abstract: High autogenous and drying shrinkage associated with the use of silica fume increases the likelihood of cracking under warm climatic conditions and limits its application as a supplementary cementitious material. This research investigates the influence of biochar, added as a partial replacement of silica fume and cement, on shrinkage, hydration, strength and permeability of cement mortar. Biochars were prepared from wood waste and coconut shell and used as 5 wt% cement replacement and 33% replacement of silica fume, respectively. It was observed that combination of biochar (5 wt% of cement) and silica fume (10 wt% of cement) can reduce autogenous shrinkage and drying shrinkage by 61% and 23% compared to the mortar with only silica fume (15 wt%) at 91-day age. By comparison, it is found that biochar with higher permeability and lower pore tortuosity lead to a higher reduction in autogenous shrinkage. Biochar from wood and coconut shell added at 5 wt% of cement has been found to improve hydration, strength and water permeability of mortar compared to control. Combination of biochar and silica fume shows improved 28-day strength compared to control mortar and offers similar strength and water permeability as that of mortar with only silica fume (15 wt%). The research outcomes highlight the benefits of using biochar in high-performance concrete which can reduce the demand for Portland cement and silica fume.